An iGlu receptor antagonist and its simultaneous use with an anticancer drug for cancer therapy - Luo, Zhong (2015)
Glutamate receptor antagonists have been known to play a crucial role in the treatment of many neuronal diseases. Recently, these antagonists have also shown therapeutic effects in the treatment of cancer. In this study, an ionotropic glutamate (iGlu) receptor antagonist, 4-hydroxyphenylacetyl spermine (L1), was used concurrently with a common anticancer drug, doxorubicin (Dox), for simultaneous cancer therapy. Mesoporous silica nanoparticles (MSNPs) were employed as the delivery vehicle for both L1 and Dox by conjugating the iGlu receptor antagonist on the surface and encapsulating Dox within the mesopores. Dox was then trapped within the mesopores by functionalizing a redox-cleavable capping group on the MSNP surface, and it could be released upon exposure to the reductive glutathione. In vitro studies on B16F10 and NIH3T3 cell lines revealed that the iGlu receptor antagonist L1 exhibited therapeutic as well as targeting effects. In addition, the simultaneous use of therapeutic L1 and Dox proved to be synergistic in the treatment of cancer. The present work demonstrated the feasibility of employing a delivery system to deliver both neuroprotective drug and anticancer drug for efficient anticancer treatment.